E-Government Reforms and Its Implications on Public Administration in Nigeria: A Case Study of the Fourth Republic - Benson, Lucky; Anjawa, Abdullahi Saleh (Kashere Journal of Politics and International Relations, 2025)
There is no doubt that Nigeria has found herself in the community where information and communication technology drives almost all governmental activities and for this reason, the regime under former president Olusegun Obasanjo has adopted e-government reforms to enable all information about government be accessed, downloaded, and informed to various citizens through the selective ministries and agencies of government. The method of data collection used in this study was the use of both primary and secondary source of data, including the researchers’ participatory observations. The paper discover the impact derived from the use of information in passing notifications on health, employment, record keeping, agendas, policy formulations and conferences/workshops attendance.